Progress in Copper-Mediated Formation of Trifluoromethylated Arenes - Liu, Tianfei; Shen, Qilong (European journal of organic chemistry, 2012)
Development of transition‐metal‐catalyzed trifluoromethylation of arene substrates under mild reaction conditions has attracted great attention in the past few years. Among the many methods developed, copper‐mediated trifluororomethylation has made significant progress and is the subject of this minireview. Recent advances in copper‐mediated trifluoromethylation of arene substrates are reviewed.